SIMULASI PENINGKATAN PENJUALAN MOBIL BEKAS PADA DEALER MOBIL “NUSANTARA” DENGAN METODE SISTEM DINAMIK - Lorenzo Andre Prasetijo; Hendra Dinata; Daniel Soesanto (CALYPTRA, 2018)
Car dealer "Nusantara" is a business that is engaged in car sales in Jember. The "Nusantara" car dealer started its operations in 2011. "Nusantara" car dealers initially operate with car sales at home and shop around to buy cars for the required stock. Development of companies in the field of car buying and selling tend to be small, due to lack of public knowledge of car dealer "Nusantara". Constraints that occur is the owner is difficult in developing in terms of product marketing. Car sales are done around, due to lack of confidence in car owner "Nusantara". Therefore, a dynamic system simulation was created in order to increase the sales of car dealer "Nusantara". The dynamic system is an approach to studying the dynamics of behavioral systems. Dynamic systems are used to analyze, design, and help improve decision making and policy formation. With the simulation of dynamic system at car dealer company "Nusantara" is expected to facilitate the owner in increasing car sales and introduce car dealer company "Nusantara" to the wider community. The dynamic system simulation of car dealer "Nusantara" is currently expected to be the owner of "Nusantara" car dealer to assist in increasing car sales.